ANALISIS KINERJA PERBANKAN DI INDONESIA : STUDI PENGUJIAN EFFICIENCY HYPOTHESIS - Kartika Sari (Jurnal Ilmiah Mahasiswa FEB, 2015)
The Indonesian  banking sector has experienced a process consolidation which has caused concerns banking performance lowering. This paper analyzes the influence of efficiency hypothesis in the Indonesian banking performance. Using data  envelopment analysis, we estimate  aset, deposit, expenses and other expenses as input and credit and net income before tax as output between for 2010-2015 in Qaurterly. The bank efficiency variabel proxy by technical efficiency (ESX) has negatif raletionship with bank performance (Return On Capital Employed) This result, therefore, no corfirms the existence of efficiency hypothesis. We proposed for  improving banking industry. They are : 1. Bank which has less efficiency should evaluate their performance by did potential improvement and establish strategic which refers to bank which has good efficiency. 2. Incentives for banks which have good efficiency.Kata kunci:Banking industry,  efficienc hyothesis .